2019
DOI: 10.21203/rs.2.10876/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Medication Burden and Inappropriate Prescription Risk Among Elderly With Advanced Chronic Kidney Disease

Abstract: Background Elderly patients with chronic kidney disease (CKD) frequently present comorbidities that put them at risk of polypharmacy and medication-related problems. This study aims to describe the overall medication profile of patients aged ≥ 75 years with advanced CKD from a multicenter French study and specifically the renally (RIMs) and potentially inappropriate-for-the-elderly medications (PIMs) that they take. Methods This is a cross-sectional analysis of medication profiles of individuals aged ≥ 75 year… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
1
4
0
4
Order By: Relevance
“…The total number of medications reported by participants in BRINK was greater than what was reported by participants in the longitudinal ARIC cohort, 20 but similar to other cohorts 35,36 . Our results are consistent with previous analyses showing frequent use of PIMs and high‐risk medications among adults with CKD 20,21,35,37 . Previous studies suggest that polypharmacy and PIM use are associated with adverse events in this population.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The total number of medications reported by participants in BRINK was greater than what was reported by participants in the longitudinal ARIC cohort, 20 but similar to other cohorts 35,36 . Our results are consistent with previous analyses showing frequent use of PIMs and high‐risk medications among adults with CKD 20,21,35,37 . Previous studies suggest that polypharmacy and PIM use are associated with adverse events in this population.…”
Section: Discussionsupporting
confidence: 89%
“…Self‐report instruments are known to be subject to social desirability and recall bias, 32 biases that may be accentuated in the setting of CI. However, all of the studies identified by the 2020 review of medication adherence in CKD used self‐reported medication adherence 21 . Self‐reported medication adherence has been associated with adverse drug events in adults with reduced eGFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 A crosssectional study of 556 elderly patients with severe renal failure found that 77% had at least one renally inappropriate medication, and 58% had at least one old-age inappropriate medication. 90 Targeted de-prescribing, which is routinely practiced in geriatric patients, has been successfully trialed as a therapeutic strategy in outpatient hemodialysis patients. 91 Although de-prescribing cannot be considered an adherence intervention, avoidable medications should be promptly discontinued to reduce the risk of adverse events, which can precipitate nonadherence.…”
Section: Ther Apy-rel Ated Interventi On Smentioning
confidence: 99%
“…Studies show that in-hospital drug related problems are on higher scale in India. 1,2 Statistical reports from studies showed the increased presence of DRP prevalence in medical sectors (45%), in a group of people differentiated by the elderly, poly-pharmacy and multimorbidity. 3 up to 40% of hospital inpatients incurred problems related to drugs, rising as the fourth -sixth main cause of death at the health care level.…”
Section: Introductionmentioning
confidence: 99%